The effects of sodium perborate tetrahydrate on digestibility and nutrient transporters in rats - Ozmen, Busra; Sahin, Emre; Tokmak, Muhammed; Kayri, Veysi; Ozmen, Ramazan; Şahin, Kazım (Tubitak Scientific & Technological Research Council Turkey, 2026)
Boron (B) is an essential micronutrient involved in hormone activity, energy metabolism, antioxidant defense, bone development, wound healing, and immune function. The present study explores the effects of sodium perborate tetrahydrate (SPT) on nutrient digestibility and the modulation of specific nutrient transporters in the jejunum and ileum of rats. A total of 40 rats were divided into four equal groups: 1) control, 2) SPT 0.5 (0.5 mg B/kg body weight [BW]), 3) SPT 1 (1 mg B/kg BW), and 4) SPT 2 (2 mg B/ kg BW), and were fed the respective diets for a period of 4 weeks. The digestibility of nutrients (dry matter, organic matter, crude protein, ether extract, ash) was determined. Subsequently, the mRNA expression of several nutrient transporters, including PepT1, SGLT1, GLUT1, GLUT2, GLUT5, FATP1, and FATP4, in the small intestine was determined using the RT-PCR method. The findings revealed that the various SPT doses influenced neither nutrient digestibility nor the expression levels of PepT1, SGLT1, GLUT1, GLUT2, GLUT5, FATP1, and FATP4 compared with the control group (p > 0.05). In conclusion, boron supplementation in the form of SPT had no effect on nutrient digestibility or the expression levels of specific nutrient transporters in the jejunum and ileum of rats.
Keywords: Boron; nutrient transporters; digestibility; sodium perborate tetrahydrate